Performance analysis of HfO2/InAlN/AlN/GaN HEMT with AlN buffer layer for high power microwave applications - Murugapandiyan, P. (H. : ĐHQGHN, 2020)
We present a performance enhancement evaluation of n þ doped graded InGaN drain/source regionbased HfO2/InAlN/AlN/GaN/AlN on SiC metal-oxide-semiconductor high electron mobility transistor (MOS-HEMTs) with a T-shaped gate. Impact on the device characteristics with the inclusion of a HfO2 surface passivation layer and an AlN buffer layer in the MOS-HEMT structure as a performance booster has been analyzed for the HEMT device with 30 nm gate length using Silvaco ATLAS TCAD. The proposed MOS-HEMT exhibits an outstanding performance, with an enhanced power gain cut-off frequency (fmax) of 366 GHz, a current gain cut-off frequency (ft) of 426 GHz, and a off-state breakdown voltage (Vbr) of 81 V. The high-k (high permittivity) HfO2 based metal oxide semiconductor HEMT device experiences a low off-state gate leakage current (Ig ~ 10 11A/mm) and a high Ion/Ioff ratio of 109. The InAlN/GaN/AlN heterostructures demonstrate improved two-dimensional electron gas (2DEG ~ 5.3 1013 cm 2), carrier mobility (m) of 1256 Cm2/V-s and drain current density of (Ids) 2.7 A/mm. A large signal analysis performed at 30 GHz yielded a maximum of 28% power-added efficiency. The high JFoM of 34.506 THz V (Johnson Figure of Merit ¼ ft Vbr) and (ft.fmax)1/2 of 394.86 GHz indicate the potential applicability of the HfO2/InAlN/GaN MOS-HEMTs in high-frequency and high-power applications.